Effect of Amomum subulatum seeds against cypermethrin induced haematological changes in wistar albino rats - Puttanna, Goutham Sagarkatte; K., Purushotham; Nayak, Swarnalatha; Rao, Eesha B.; Mundugaru, Ravi (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Cypermethrin is a well know agricultural pesticide used in the developing countries. It is associated with significant toxic potential on human health. Hence the present study was aimed to evaluate the protective role of Amomum subulatum against cypermethrin induced haematalogical changes in Wistar albino rats. Methods: The albino rats were divided into five different groups of six rats each. Group I considered as normal control, group II cypermethrin control (25mg/kg body weight p.o.), group III only test drug and group IV and V administered with cypermethrin 25mg/kg body weight along test drug 1.08 and 2.16mg/kg body weight for 28 consecutive days. At the end of 28th day blood was withdrawn and total haematalogical parameters were estimated. Results: In the cypermethrin control there was significant reduction in the WBC, Platelet, MCHC and considerable reduction in the haemoglobulin concentration in comparison to normal control. The test drug administered at both dose levels was significantly reversed the cypermethrin induced changes in haematalogical parameters. Conclusions: Authors can conclude that the Amomum subulatum has potency to reverse the cypermethrin induced haematalogical changes.